The impact of brain network microstructural changes on upper limb mirror movements after stroke - Dai, Jie; Li, Zhaoqing; Tao, Jingyan; Sun, Shuping; Li, Jianhua (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigate the relationship between brain network microstructural changes and surface electromyographic (sEMG) signs of upper limb mirror movements (MMs) in stroke patients, focusing on the corpus callosum and bilateral corticospinal tracts (CSTs).MethodA retrospective analysis was conducted on 48 stroke patients (mean age 60.63y, range 15-83y) who underwent sEMG and diffusion tensor imaging (DTI). All the stroke patients were in the subacute to chronic phase. sEMG parameters, including overflow percentage (OF) and standardized net excitation (SNE), were measured during unilateral maximum contraction tasks. DTI metrics, such as fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD), were analyzed in the corpus callosum and bilateral CSTs. All DTI metrics were processed and computed using FSL (FSL, version 5.0.5). Correlation analyses were performed between sEMG parameters, DTI metrics, and clinical data.ResultsThere was a significant asymmetry in motor overflow between affected and unaffected limbs, with higher OF and SNE in the unaffected limb during affected limb movement. The RCI (right-sided cerebral infarction) group showed more pronounced MMs compared to the LCI (left-sided cerebral infarction) group. The DTI metrics were closely related to age and disease duration. In the LCI group, a negative correlation was found between FA values of the corpus callosum and MMs, and between FA of the CST and MMs in the affected limb.ConclusionThe study demonstrated that sEMG manifestations of MMs could reflect the motor function of the affected upper limb in stroke patients. Microstructural changes to the corpus callosum and CSTs might be one of the causes of the post-stroke MMs.